Reading Autobiography : A Guide for Interpreting Life Narratives, Second Edition - Smith, Sidonie (Book collections on Project MUSE., 2010)
Thoroughly updated, the second edition of Reading Autobiography is the most complete assessment of life narrative in its myriad forms. Sidonie Smith and Julia Watson lay out a sophisticated, theoretical approach to life writing and the components of autobiographical acts, including memory, experience, identity, embodiment, space, and agency.